Leadership and business model innovation in late internationalizing SMEs. Issue 1 (February 2022) - Colovic, Ana
Abstract: Drawing on the distinction between small-scale and large-scale business model innovation, and between directive and empowering leadership, we examine how CEOs in SMEs lead business model innovation during the process of internationalization. Building on eight cases of Japanese manufacturing SMEs, we develop a theoretical framework pointing to two different patterns in the articulation between CEO leadership style and business model innovation. We show that small-scale business model innovation led by directive leadership results in a timelier foreign market entry. However, in order to increase international sales, large-scale business model innovation is required. This is facilitated by an empowering leadership style of the CEO.